TO A QUESTION OF FEASIBILITY OF APPLICATION OF 100 HZ VIBRATION IN TREATMENT AND REHABILITATION OF THE PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - T. N. Zaripova; M. A. Serebrova; I. I. Antipova (Бюллетень сибирской медицины, 2016)
The aim of this research is study of feasibility of application of instrumental 100 Hz vibration of the thorax for rehabilitation of COPD patients.Materials and methods. This aim is achieved by clinical observation of 43 COPD patients of 1st and 2nd severity, 77.4 % from which were patients with low risk of exacerbations. Research has been carried out during the stable period of disease. The following parameters have been analyzed: dynamics of the clinical state, spirometry data, clinical - biochemical indicators of blood reflecting presence of the inflammatory process activity, a number of indicators of immune system. Two groups of patients, which were equivalent in an initial state on age, disease severity, expressiveness of functional violations, have been isolated. The 1st group contained 20 persons was the main one. It received 100 Hz vibration impact on the thorax on the background of exercises with physical therapy and inhalations of physiological solution. The 2nd group contained 23 persons obtained in addition sea-buckthorn paste.Results. It has been revealed that the course of 100 Hz vibration impact on the thorax is accompanied, mainly, with positive subjective dynamics in the form of decrease of frequency and expressiveness of complaints. At that it has been noted improvement of bronchial passability due to improved drainage of bronchial tubes, but only at the patients with initial violations of ventilation. Only additional reception of sea-buckthorn paste on the background of vibrotherapy contributes to decrease of subclinical inflammation activity and strengthening of immunological protection. Essential positive results of treatment have been reached only for a half of the surveyed patients that allows to speak about non-expediency or low expediency of use of 100 Hz vibration for CODT patients even 1st and 2nd severity in the stable period of course of the disease.